Digital Storytelling to Enhance Adults’ Speaking Skills in Learning Foreign Languages: A Case Study. - Kallinikou, Emily; Iolie Nicolaidou (My University, 2019)
Digital storytelling, including text, images, audio, music, and video, has been researched as a means of enhancing learners’ motivation, autonomy, and engagement and as a way to improve oral and speaking skills in foreign language learning. This study examined the relation between adults’ engagement in digital storytelling (scaffolded by an interactive learning environment) and their speaking skills and motivation when learning a foreign language. The study used a pre-test, post-test control group design with two groups of 20 Russians who were beginners in learning Greek as a foreign language (n = 40). The 12-h intervention was technology-supported only for the experimental group. Even though the comparison of participants’ recorded speech pre- and post-intervention revealed a statistically significant decrease of mistakes made during speech from pre- to post-intervention for both groups, an independent samples t-test to compare the groups’ post-intervention speaking performance revealed a statistically significant difference in favor of the experimental group (t(38) = 4.05, p < 0.05). The analysis of results from a motivation questionnaire administered pre- and post-intervention showed a statistically significant increase in the motivation of the experimental group only. Findings provide an indication that digital storytelling, scaffolded by an interactive learning environment, supports the development of adults’ speaking skills in a foreign language and increases their motivation.
Keywords: Interaction and mobile devices; Digital storytelling; Speaking skills; Motivation; Adult education; Web-based learning environment